PENGARUH KUALITAS AUDIT DAN KOMPETENSI KOMITE AUDIT TERHADAP MANAJEMEN LABA DENGAN MANIPULASI LABA SEBAGAI VARIABEL MODERASI - Nurul Hudiani; Vinola Herawaty (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The aim of this research is empirically to find out the influence of the the effect of audit quality and competence the audit committee on firm value with earning manipulation as moderation variable. Controlling variabels firm size control variables and leverage.Sampel on this research is property, real estate and contruction company listed on Bursa Efek Indonesia for period 2011 – 2016. Based on purposive sampling, sampel that used for this research is 40 company with six year period, with the number of observations as many as 240 samples but there are 7 outliers samples, so the end of 233 samples. Analysis data method that used by multiple regression analysis.The result of the research concludes that the competence of audit committee has positive influence to firm value and earnings manipulation weakens the positive influence of the competence of audit committee on the firm value, while audit quality variable has no positive effect to firm value and earnings manipulation does not weaken the positive effect of audit quality on firm value.